(untitled) (Herald of Journalism, 2018)
The article tells about important factors in the training of specialists in the field of PR. The main purpose of the article is to identify and classify aspects of public relations. Specialist in the field of PR - is responsible for the image of the company and therefore it is necessary to take seriously and responsibly the training of specialists. This profession is exclusive and it is gaining momentum among large companies. Image is often seen in two foreshortenings: as “face” or “mask”, image or mask. The field of activity of PR specialists is not only communication with the media, but also the formation of the company’s policy, participation in the development of its strategy, organization of events, fundraising for non-profit organizations and work related to the internal PR organization. In his professional activities, a PR specialist builds a variety of communications. These are organization of press conferences and other events with journalists, the participation of the organization’s top officials in secular and protocol events and much more. In principle, PR-specialist is the face of the company. Key words: image, PR-specialist, public relations, image formation, reputation.